An exploratory study of discourse conventions in the European Parliament: Thanking in Spanish, French and Dutch Un estudio exploratorio de las convenciones discursivas en el parlamento europeo: los agradecimientos en español, francés y neerlandés - Patrick Goethals; Babette Blancke (Revista de Lingüística y Lenguas Aplicadas, 2013)
In this paper, we analyze a small-scale corpus with Spanish, French and Dutch interventions in the plenary debates in the European Parliament, in order to verify whether there exist cultural differences in the use and the expression of the particular politeness strategy of thanking somebody. We find that thanking is more frequent in Spanish and French than in Dutch. In addition, it plays a more prominent role, e.g. because the acknowledgements are longer and receive more emphasis. Previous studies found that Dutch speakers tend to use many routine acknowledgements in contexts where there may be a threat to the negative face of one of the speech participants. Our study shows that French and Spanish speakers use more acknowledgements than Dutch when public positive face is at stake. The data also show the relevance of the concept of valuating politeness, as opposed to mitigating politeness, in order to describe the Spanish data. En este trabajo analizamos un corpus piloto de intervenciones españolas, francesas y neerlandófonas en los debates plenarios del Parlamento Europeo, con el fin de averiguar si existen diferencias interculturales en cuanto al uso y la expresión de una estrategia de cortesía particular, que son los agradecimientos. Comprobamos que los agradecimientos figuran con mayor frecuencia en los discursos de los españoles y los franceses que en los discursos de los neerlandófonos. Además, cobran más relieve, por ejemplo porque son más extensos y se enfatizan más. Estudios anteriores han observado que los neerlandófonos tienden a usar muchos agradecimientos rutinarios en contextos donde podría existir una amenaza para la imagen negativa de uno de los interlocutores. Nuestro estudio muestra que los franceses y los españoles usan más agradecimientos que los neerlandófonos cuando está en juego la imagen positiva. Los datos apuntan además hacia la relevancia del concepto de la cortesía valorizante, por oposición a la cortesía mitigadora, para describir los datos españoles.